New drug classes for the treatment of partial onset epilepsy: focus on perampanel - Shih JJ; Tatum WO; Rudzinski LA (Dove Medical Press, 2013)
Jerry J Shih,1 William O Tatum,1 Leslie A Rudzinski21Department of Neurology, Mayo Clinic, Jacksonville, FL, USA; 2Department of Neurology, Emory University, Atlanta, GA, USAAbstract: Perampanel (2-[2-oxo-1-phenyl-5-pyridin-2-yl-1,2-dihydropyridin-3-yl] benzonitrile hydrate) is the latest in the line of new antiepileptic drugs with a novel mechanism of action. Perampanel inhibits α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA)-induced increases in intracellular Ca2+ and selectively blocks AMPA receptor-mediated synaptic transmission, thus reducing neuronal excitation. Three Phase III multicenter, randomized, double-blind, placebo-controlled trials demonstrated the efficacy and good tolerability of perampanel as adjunctive treatment in patients with refractory partial-onset seizures. The drug is approved for use in the European Union and United States, with expected release onto the American market in June–September 2013, pending US Drug Enforcement Agency classification. The pharmacology of perampanel offers potential as more than just another new antiepileptic drug. This first-in-class drug will provide another option for practitioners of rational polytherapy. As an AMPA-receptor antagonist, perampanel may possess antiepileptogenic properties in addition to its demonstrated antiseizure properties.Keywords: perampanel, mechanism of action, efficacy, review